Corpus Linguistics, Network Analysis and Co-occurrence Matrices Corpus Linguistics, Network Analysis and Co-occurrence Matrices - Keith Stuart; Ana Botella (International Journal of English Studies (IJES), 2009)
This article describes research undertaken in order to design a methodology for the reticular representation of knowledge of a specific discourse community. To achieve this goal, a representative corpus of the scientific production of the members of this discourse community (Universidad Politécnica de Valencia, UPV) was created. The article presents the practical analysis (frequency, keyword, collocation and cluster analysis) that was carried out in the initial phases of the study aimed at establishing the theoretical and practical background and framework for our matrix and network analysis of the scientific discourse of the UPV. In the methodology section, the processes that have allowed us to extract from the corpus the linguistic elements needed to develop co-occurrence matrices, as well as the computer tools used in the research, are described. From these co-occurrence matrices, semantic networks of subject and discipline knowledge were generated. Finally, based on the results obtained, we suggest that it may be viable to extract and to represent the intellectual capital of an academic institution using corpus linguistics methods in combination with the formulations of network theory. En este artículo describimos la investigación que se ha desarrollado en el diseño de una metodología para la representación reticular del conocimiento que se genera en el seno de una institución a partir de un corpus representativo de la producción científica de los integrantes de dicha comunidad discursiva, la Universidad Politécnica de Valencia.. Para ello, presentamos las acciones que se realizaron en las fases iniciales del estudio encaminadas a establecer el marco teórico y práctico en el que se inscribe nuestro análisis. En la sección de metodología se describen las herramientas informáticas utilizadas, así como los procesos que nos permitieron disponer de aquellos elementos presentes en el corpus, que nos llevarían al desarrollo de matrices de co-ocurrencias con las que se generaron redes semánticas del conocimiento disciplinar. Finalmente, a partir de los resultados obtenidos, constatamos la viabilidad de extraer y representar el capital intelectual basándonos en los principios de la lingüística de corpus en combinación con las formulaciones de la teoría de redes.